The usual suspects - Broaddus, Maurice (Katherine Tegen Books, 2020)
When a gun is found at a park near Thelonius Mitchell's school, he and his friend, Nehemiah, are among the first to be suspected. The boys have a history of causing trouble and spend their school days in a special education classroom because they've been labeled as being "emotionally delinquent." But while they may be pranksters, they don't want to add the label "criminal" to the list, and they're determined to uncover the truth in order to clear their names.